Analisis Asuhan Keperawatan Demensia Dengan Masalah Defisit Perawatan Diri Di Griya Lansia Jannati Provinsi Gorontalo - Polohi, Fikria (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Entering old age means experiencing decline, for example physical decline which is characterized by sagging skin, graying hair, teeth starting to become toothless, hearing less clear, eyesight getting worse, slow movements, disproportionate body figure and memory becoming weak or senile. The aim of this study forknow the process of assessing, diagnosing, planning, implementing, documenting and evaluating elderly people with dementia at Home for the Elderly Jannati, Gorontalo Province. Methods: The design of this research is to use a case study research design (nursing care) including nursing assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. Results: From the results of the assessment and examination carried out on the three clients, it was found that they had dementia with self-care deficits. The main problem that emerged in all respondents was dementia with self-care deficits. So the nursing diagnosis that emerged was memory impairment and self-care deficit. The implementation carried out by the author is with the mini mental state exam (MMSE), short portable mental status questionnaire (SPMSQ), and puzzle therapy for dementia. Meanwhile, for self-care deficits, there are Self-Care Education pamphlets (how to maintain body hygiene). Overall evaluation, after the nursing actions were carried out, it was found that there was an increase in knowledge related to dementia with self-care deficits in respondents and the ability to carry out good personal hygiene. Conclusion:This research describes nursing care, namely discussing the similarities and differences between nursing diagnoses and theory from 3 similar cases at the Griya Jannati Home for the Elderly. By using a comprehensive nursing process, starting from assessment, establishing a nursing diagnosis, making plans to determine goals and outcome criteria, implementation, evaluation and documentation.